Conceptions of health education practices in the context of Nursing Education - Sâmia Jucá Pinheiro; Francisca Ediquelle Queiroz Lucas; Luciana de Fátima Barreto; Monara Rochelle Cordeiro Marinho Cruz; Francisco Gilberto Fernandes Pereira; Andréa Lopes Barbosa (Rev Rene)
Objective: to understand health education practices in the context of nursing education.Methods: a qualitative study held in a private Higher Education Institution. The participants were 22 subjects who answered a semi-structured interview, whose information was organized and analyzed by the content analysis method. Results: three categories were identified: health education and the nurse as an educator; health education in primary care; and comparison of educational practices in levels of care. Conclusion: the students understood the importance of health education in their training, and felt the need to expand these practices to all health care levels.